A new medium containing mupirocin, acetic acid, and norfloxacin for the selective cultivation of bifidobacteria - Vlková, Eva; Salmonová, Hana; Bunešová, Věra; Geigerová, Martina; Rada, Vojtěch; Musilová, Šárka (Anaerobe, 2015)
Various culture media have been proposed for the isolation and selective enumeration of bifidobacteria. Mupirocin is widely used as a selective factor along with glacial acetic acid. TOS (transgalactosylated oligosaccharides) medium supplemented with mupirocin is recommended by the International Dairy Federation for the detection of bifidobacteria in fermented milk products. Mupirocin media with acetic acid are also reliable for intestinal samples in which bifidobacteria predominate. However, for complex samples containing more diverse microbiota, the selectivity of mupirocin media is limited. Resistance to mupirocin has been demonstrated by many anaerobic bacteria, especially clostridia. The objective was to identify an antibiotic that inhibits the growth of clostridia and allows the growth of bifidobacteria, and to use the identified substance to develop a selective cultivation medium for bifidobacteria. The susceptibility of bifidobacteria and clostridia to 12 antibiotics was tested on agar using the disk diffusion method. Only norfloxacin inhibited the growth of clostridia and did not affect the growth of bifidobacteria. Using both pure cultures and faecal samples from infants, adults, calves, lambs, and piglets, the optimal concentration of norfloxacin in solid cultivation media was determined to be 200 mg/L. Our results showed that solid medium containing norfloxacin (200 mg/L) in combination with mupirocin (100 mg/L) and glacial acetic acid (1 mL/L) is suitable for the enumeration and isolation of bifidobacteria from faecal samples of different origins.
Keywords: Culture Media; mupirocin; Norfloxacin; norfloxacin; kojenec; Middle Aged; Bifidobacterium; Bacteriological Techniques; Infant; lodě; Mupirocin; Adult; bakteriologické techniky; Microbial Sensitivity Tests; skot; Acetic Acid; kyselina octová; Clostridia; Swine; Ships; zvířata; Humans; Cattle; kultivační média; lidé středního věku; Cultivation media; prasata; Antibiotics; dospělí; mikrobiální testy citlivosti; Bifidobacteria; lidé; Animals